2010
DOI: 10.1002/jgm.1496
|View full text |Cite
|
Sign up to set email alerts
|

RH10 provides superior transgene expression in mice when compared with natural AAV serotypes for neonatal gene therapy

Abstract: Background-Neonatal gene therapy is a promising strategy for treating diseases diagnosed before or shortly after birth. Early and long-term expression of therapeutic proteins may limit the consequences of genetic mutations and result in a potential 'cure'. Adeno-associated viral vectors have shown promise in many areas of adult gene therapy but their properties have not been systematically investigated in the neonate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
94
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(96 citation statements)
references
References 52 publications
1
94
1
Order By: Relevance
“…Finally, neonatal immune immaturity (particularly of B cells) may result in blunted immune responses to the vector or the transgene, and may induce B cell immune tolerance. [15][16][17] Earlier studies conducted in our laboratory demonstrated that AAV serotype rh10 led to greater maintenance of copy number in the liver 18 and led to the selection of this serotype as a gene delivery vector for these studies. Knowing that the copy number would decline rapidly following the initial neonatal injection, animals received a second injection when they reached a weight of 10 g (about day 20 of life).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, neonatal immune immaturity (particularly of B cells) may result in blunted immune responses to the vector or the transgene, and may induce B cell immune tolerance. [15][16][17] Earlier studies conducted in our laboratory demonstrated that AAV serotype rh10 led to greater maintenance of copy number in the liver 18 and led to the selection of this serotype as a gene delivery vector for these studies. Knowing that the copy number would decline rapidly following the initial neonatal injection, animals received a second injection when they reached a weight of 10 g (about day 20 of life).…”
Section: Discussionmentioning
confidence: 99%
“…11,14 Among these new vectors, AAV-rh10 showed high efficacy to transduce neurons in adult and neonatal rodent brain. 11,[15][16][17][18] AAV-rh10-mediated transduction of other cell types has not been thoroughly examined.…”
Section: Introductionmentioning
confidence: 98%
“…Indeed recent studies have shown long term safety and transgene expression for over 5 years in a large cohort of non human primates systemically injected with AAV8 based vectors [34]. In addition, persistent transgene expression and safety were also shown after neonatal mice intravenous injection of AAV based vectors, including AAV8 [35]. Our studies show the potential of gene therapy to treat GNE myopathy using an AAV8 based platform.…”
Section: Discussionmentioning
confidence: 58%